Скасування запобіжного заходу у зв’язку з прийняттям уповноваженим органом рішення про передачу підозрюваного, обвинуваченого для обміну як військовополоненого: процесуальний порядок і проблемні питання - Фоміна, Т. Г.; Fomina, T. H.; Тетяна Фоміна (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 194-205, 2022)
Враховуючи необхідність врегулювання процедури обміну осіб як військовополонених у межах кримінального провадження, законодавець цілком обґрунтовано та вчасно унормував це питання шляхом ухвалення 28 липня 2022 р. Закону України «Про внесення змін до Кримінального, Кримінального процесуального кодексів України та інших законодавчих актів України щодо врегулювання процедури обміну осіб як військовополонених» № 2472-IX. Проаналізовано законодавчі новели щодо порядку скасування запобіжного заходу у зв’язку з прийняттям уповноваженим органом рішення про передачу підозрюваного, обвинуваченого для обміну як військовополоненого, визначено процесуальний порядок такого скасування та зосереджено увагу на прийнятті рішення про передачу підозрюваного, обвинуваченого для обміну як військовополоненого як підстави такого скасування. Виокремлено проблемні питання щодо нормативного врегулювання скасування запобіжного заходу в порядку ст. 201-1 КПК України та запропоновано їх вирішення.

Taking into account the need to regulate the procedure of exchanging persons as prisoners of war within the framework of criminal proceedings, the legislator fully justified and timely regulated this issue by adopting on July 28, 2022 the Law of Ukraine “On Amendments to the Criminal and Criminal Procedural Codes of Ukraine and other legislative acts of Ukraine regarding the regulation of the exchange procedure persons as prisoners of war” No. 2472- IX. The addition of the new Article 201-1 to the Criminal Procedure Code of Ukraine contributed to the establishment of the procedure for the cancellation of a preventive measure in connection with the adoption by an authorized body of a decision on the transfer of a suspect, an accused person for exchange as a prisoner of war. The legislative amendments regarding the procedure for canceling a preventive measure in connection with the adoption by an authorized body of a decision to hand over a suspect, an accused person for exchange as a prisoner of war, have been analyzed. The procedural order of such cancellation has been defined and attention has been focused on the decision to transfer the suspect, the accused for exchange as a prisoner of war as a basis for such cancellation. Problematic issues regarding the normative regulation of the cancellation of a preventive measure in accordance with Art. 201-1 of the Criminal Procedure Code of Ukraine and their solution has been proposed. Revealing the issue regarding the order of implementation of Art. 201-1 of the Criminal Procedure Code of Ukraine, it has been determined that the cancellation of the preventive measure is carried out by the investigating judge, the court at the request of the prosecutor. The basis for the prosecutor’s appeal to the investigating judge, the court with the relevant request is the decision of the authorized body to transfer the suspect, the accused for exchange as a prisoner of war. At the same time, the law does not require the decision of the authorized body to transfer the suspect, the accused for exchange as a prisoner of war to the investigating judge, the court; the prosecutor must provide materials confirming the adoption of such a decision. The peculiarity of such a petition consideration is that the law does not require the participation of a person in respect of whom an authorized body has made a decision to exchange as a prisoner of war during the court session. It has been proven that the normative regulation of the cancellation of a preventive measure needs improvement, in particular with regard to: 1) the title of Article 201-1 of the Criminal Procedure Code of Ukraine, which should be read as “Cancellation of a preventive measure in connection with the adoption by an authorized body of a decision on the transfer of a suspect, accused for exchange as a prisoner of war”, since its current title is broader than its content; 2) legislative settlement of the consequences of the cancellation of a preventive measure in the event that the exchange of a prisoner of war is not carried out

Учитывая необходимость урегулирования процедуры обмена лиц как военнопленных в рамках уголовного производства, законодатель вполне обоснованно и своевременно унормировал этот вопрос путем принятия 28 июля 2022 г. Закона Украины «О внесении изменений в Уголовный, Уголовный процессуальный кодекс Украины и другие законодательные акты Украины об урегулировании процедуры обмена лиц как военнопленных» №2472-IX. Проанализированы законодательные новеллы относительно порядка отмены меры пресечения в связи с принятием уполномоченным органом решения о передаче подозреваемого, обвиняемого для обмена как военнопленного, определен процессуальный порядок такой отмены и сосредоточено внимание на принятии решения о передаче подозреваемого, обвиняемого для обмена как военнопленного как основание такой отмены. Выделены проблемные вопросы нормативного урегулирования отмены меры пресечения в порядке ст. 201-1 УПК РФ и предложено их решение.
Cancellation of a preventive measure in connection with the adoption by an authorized body of a decision on the transfer of a suspect, an accused person for exchange as a prisoner of war: procedural order and problematic issues
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; кримінально-процесуальне законодавство; criminal procedural legislation; уголовно-процессуальное законодательство; воєнний стан; martial law; военное положение; запобіжний захід; precaution; мера пресечения; військовополонений; prisoner of war; военнопленный; рішення уповноваженого органу про передачу підозрюваного, обвинуваченого для обміну як військовополоненого; скасування запобіжного заходу; cancellation of preventive measure; отмена меры пресечения